Aktivitas Komunikasi Pemasaran Melalui Akun Instagram (Studi Pada Staff dan Pengelola Akun Pelindo Daya Sejahtera) - Marissa ono Damayanti; Widiya Yutanti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
In the current modern era and in the midst of the complicated Covid-19 pandemic, every company is required to think creatively and innovatively where social media plays an important role in marketing communication activities, one of which is Instagram social media as a way to carry out Marketing Communication Activities. By using a qualitative approach with the type of descriptive research. And using interview data collection techniques, documentation, and literature study. Supported by a planning theory approach which is one of the models for compiling messages to achieve the goals of marketing communications. It can be concluded that better marketing communication is carried out by utilizing the 4P Marketing mix principle through Instagram social media, it will also have an impact on the effectiveness of promotions and the targets of managers and staff will be met.